K-State Turfgrass Research 2005 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2005)
Turfgrass Research 2005 contains results of projects done by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 4, 2005, at the Rocky Ford Turfgrass Research Center in Wichita. The enclosed articles present summaries of research projects that were completed recently or will be completed in the next year or two. This year's report presents summaries of research on environmental stresses, turfgrass establishment and culture, and cultivar evaluations.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 2005; Kansas Agricultural Experiment Station contribution; no. 05-306-S; Turfgrass; Environmental stress; Cultivar evaluations; Pest management; Bluegrass; Buffalograss; Bermudagrass; Tall Fescue; Creeping Bentgrass; Zoysiagrass